2015
DOI: 10.3758/s13423-015-0883-7
|View full text |Cite
|
Sign up to set email alerts
|

Not all memories are the same: Situational context influences spatial recall within one’s city of residency

Abstract: Reference frames in spatial memory encoding have been examined intensively in recent years. However, their importance for recall has received considerably less attention. In the present study, passersby used tags to arrange a configuration map of prominent city center landmarks. It has been shown that such configurational knowledge is memorized within a north-up reference frame. However, participants adjusted their maps according to their body orientations. For example, when participants faced south, the maps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This finding is somewhat consistent with previous literature on representational flexibility in that navigators acquire allocentric and egocentric spatial knowledge in parallel (Brunyé et al 2008 ; Iglói et al 2009 ). Although all participants learned the environment from the same perspective, individual differences and different learning goals might determine that participants performed differently at egocentric and allocentric spatial knowledge (Meilinger et al 2016 ; Pazzaglia and Taylor 2007 ). This finding was also likely due to the specific measure chosen to assess environmental distance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is somewhat consistent with previous literature on representational flexibility in that navigators acquire allocentric and egocentric spatial knowledge in parallel (Brunyé et al 2008 ; Iglói et al 2009 ). Although all participants learned the environment from the same perspective, individual differences and different learning goals might determine that participants performed differently at egocentric and allocentric spatial knowledge (Meilinger et al 2016 ; Pazzaglia and Taylor 2007 ). This finding was also likely due to the specific measure chosen to assess environmental distance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, perceived and traversed distance are egocentric, whereas environmental distance is allocentric. Previous literature on representational flexibility has found that navigators acquire allocentric and egocentric spatial knowledge in parallel (Brunyé et al 2008 ; Iglói et al 2009 ) and that both learning perspective and learning goal (as well as individual differences) influence cognitive map development (Meilinger et al 2016 ; Pazzaglia and Taylor 2007 ). In an outdoor setting, Ishikawa and Montello ( 2006 ) found that, after participants built more accurate metric knowledge of the space by integrating separately learned routes, traversed distance estimates were not improved.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these dependencies, the bodily orientation of the subjects might also play a role. This was demonstrated by Meilinger, Frankenstein, Simon, Bülthoff, and Bresciani (2016) using a building task instead if freely sketched maps. Subjects were given a set of cards naming popular locations around town and asked to rebuild the configuration.…”
Section: Introductionmentioning
confidence: 99%
“…The study confirms the position dependence of the recall orientation and additionally demonstrates an effect of body orientation. Note, however, that the Meilinger et al (2016) study uses landmark buildings in a larger area, not views of a single city square. The building task was transferred to a virtual environment by Le Vinh, Meert, and Mallot (2020), again with the reconstruction of a specific target square as a task.…”
Section: Introductionmentioning
confidence: 99%
“…In all of the situations described above, perceptually available information is not sufficient, but has to be augmented by spatial information from working and long‐term memory to achieve one's goal. Accordingly, the characteristics of IPT performance indicate characteristics of the involved processes and representations, and a considerable body of previous research has employed IPT to investigate the aspects of spatial memory (e.g., Brockmole & Wang, 2003; Farrell & Robertson, 1998; Giudice, Klatzky, & Loomis, 2009; Kelly, Siegel, Sjolund, & Avraamides, 2018; Meilinger, Frankenstein, Simon, Bülthoff, & Bresciani, 2016; Newman, Cox, & McNamara, 2021; Presson & Montello, 1994; Puls & May, 2020; Riecke & McNamara, 2017; Rieser, 1989; Sholl, 2001; Waller & Hodgson, 2006; Warren, Rothman, Schnapp, & Ericson, 2017).…”
mentioning
confidence: 99%